2014
DOI: 10.1080/19338244.2013.863752
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Asbestos Exposure and Lung Cancer—A Systematic Review of the Literature

Abstract: The objective of this study was to evaluate the scientific literature concerning asbestos and lung cancer, emphasizing low-level exposure. A literature search in PubMed and Embase resulted in 5,864 citations. Information from included studies was extracted using SIGN. Twenty-one statements were evidence graded. The results show that histology and location are not helpful in differentiating asbestos-related lung cancer. Pleural plaques, asbestos bodies, or asbestos fibers are useful as markers of asbestos expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 92 publications
0
78
0
4
Order By: Relevance
“…In 1997, the Helsinski criteria for identifying individuals with a high risk of asbestos exposure at work were accepted (2). Older studies found inconsistent results regarding the lobe of origin and histology of asbestos-related lung cancer (ARLC) (3). Some studies showed an upper lobe location similar to tobacco-related lung cancer, whereas other investigators found a lower lobe location (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, the Helsinski criteria for identifying individuals with a high risk of asbestos exposure at work were accepted (2). Older studies found inconsistent results regarding the lobe of origin and histology of asbestos-related lung cancer (ARLC) (3). Some studies showed an upper lobe location similar to tobacco-related lung cancer, whereas other investigators found a lower lobe location (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Pleural plaques are widely referred to (Attanoos & Gibbs, 2009;Dalphin, 2011;Dweik & Mazzone, 2010;Edelman, 1988;Gevenois & De Vuyst, 2006;Fishwick & Barber, 2014;Hourihane et al, 1966;IIAC, 2008;Moolgavkar et al, 2014;Nielsen et al, 2014) as ''markers of asbestos exposure 9 '' or an index or ''signpost'' (Sargent et al, 1977) of exposure meaning that (other things being equal) an asbestos-exposed person that develops a pleural plaque is likely to have had greater asbestos exposure than someone without a plaque. 10 Thus, even if the development of pleural plaques is an entirely independent process from the development of malignant effects, such as lung cancer or mesothelioma, it is likely that there will be a correlation between pleural plaques and other serious endpoints, including lung cancer or mesothelioma.…”
Section: Pleural Plaques As Markers Of Exposurementioning
confidence: 99%
“…Ameille et al (41) in the French National Monitoring Program reported an estimated annual incidence of lung cancer in asbestos-exposed workers between 2,086 and 4,172 (1990) and an annual MPM incidence between 646 and 800 [1998][1999][2000][2001][2002][2003]. Moreover, it is known that the interaction between asbestos exposure and smoking habit has an additive or multiplicative effect for developing lung cancer (42).…”
Section: Discussionmentioning
confidence: 99%